Interpretasi Karakteristik Dewa Siwa Sebagai Inspirasi Seni Lukis - Sadewa, Kadek Ian Gangga; Adnyana, I Wayan; Yudha, I Made Bendi (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2024)
This thesis contains a description of the creation of painting with the theme